Analisis Pengaruh Pelatihan Kerja dan Penilaian Prestasi Kerja Terhadap Produktivitas Kerja Karyawan Pada PT Sinde Budi Sentosa - Angkoso Mukti, Ferdi; Waluya, Sri; Sianturi, Murdan (Mulia Pratama, 2024)
This research aims to find out how much influence work training and work performance assessment have on employee work productivity at PT. Sinde Budi Sentosa. The population in this research was employees of PT. Sinde Budi Sentosa. The sample in this research was 30 employees. The data collection technique in this research was carried out by administering a questionnaire. Data were analyzed using multiple linear regression analysis, analysis of the coefficient of determination, t test and f test using SPSS. The results of the multiple linear regression analysis obtained a value of Y = 10.591 + 0.460 X1 + 0.287 X2 Then the job training coefficient value is 0.460, meaning that if job training increases by one percent, employee work productivity will increase by 0.460 percent provided that the other independent variables are fixed. Meanwhile, the work performance assessment coefficient value is 0.287, meaning that if the work performance assessment increases by one percent, then employee work productivity will increase by 0.287 percent provided that the otherindependent variables are fixed. The coefficient of determination test result (R2) = 0.665. The results show that the Job Training and Job Performance Evaluation variables have a 66.5% influence on employee work productivity, while the remaining 33.5% is influenced by other variables that were not studied. Based on the data analysis carried out, it was concluded that in partial testing( t test) via SPSS it was seen that the results of the job training sig value (X1) on employee work productivity showed Tcount > Ttable (2.221 > 2.052). H0 is rejected, so it can be concluded that the influence of job training variable has a positive effect on employee work productivity variables. The results of testing the work performance assessment variable (X2) on employee work productivity (Y) show Tcount < Ttable (1.669 < 2.052). H0 is accepted, so it can be concluded that the variable influence of partial work performance assessment has no effect on the employee work productivity variable. Based on the results of comprehensive testing (f test) via SPSS, it can be seen from the sig results of 0.001 < 0.05. So the independent variables job training and job performance assessment (independent) have a significant effect on the dependent variable employee work productivity (dependent). The overall results of data management using SPSS can be concluded that the independent variable worktraining (X 1) has a positive and significant effect on employee work productivity while the work performance assessment variable (X2) does not have a positive and significant effect on the dependent variable employee work productivity.